2013
DOI: 10.1088/1367-2630/15/1/013058
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic scattering and duality in the one-dimensional three-state quantum Potts model on a lattice

Abstract: We determine numerically the single-particle and the two-particle spectrum of the three-state quantum Potts model on a lattice by using the density matrix renormalization group method, and extract information on the asymptotic (small momentum) S-matrix of the quasiparticles. The low energy part of the finite size spectrum can be understood in terms of a simple effective 8 In the continuum limit, the properties of the Potts model are usually described by the so-called scaling Potts field theory, which is a pert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(120 reference statements)
0
12
0
Order By: Relevance
“…A detailed DMRG analysis has shown that the observed discrepancy between the factorized S matrix and the low-energy scattering of quasi-particles in the discrete spin chain persists even non-perturbatively [31], and it was speculated that this was due to the presence of an irrelevant operator that has a large effect on the low-energy limit of the scattering amplitudes away from the scaling limit. In this connection, first of all we note that the raw TCSA phase-shifts in figures 5.3, 5.4 and 5.5 show a characteristic deviation from the field theory predictions at low energies which is very similar to that observed in the DMRG results of [31]. In contrast to the DMRG study, in this paper we are in a position to identify the source of this deviation: it originates from the cut-off dependence introduced by the operators that appear in the OPE The counter term from the identity I is the universal contribution shown explicitly in (3.69), which only renormalizes the bulk energy density and thus makes no contribution to the extracted phase-shifts.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A detailed DMRG analysis has shown that the observed discrepancy between the factorized S matrix and the low-energy scattering of quasi-particles in the discrete spin chain persists even non-perturbatively [31], and it was speculated that this was due to the presence of an irrelevant operator that has a large effect on the low-energy limit of the scattering amplitudes away from the scaling limit. In this connection, first of all we note that the raw TCSA phase-shifts in figures 5.3, 5.4 and 5.5 show a characteristic deviation from the field theory predictions at low energies which is very similar to that observed in the DMRG results of [31]. In contrast to the DMRG study, in this paper we are in a position to identify the source of this deviation: it originates from the cut-off dependence introduced by the operators that appear in the OPE The counter term from the identity I is the universal contribution shown explicitly in (3.69), which only renormalizes the bulk energy density and thus makes no contribution to the extracted phase-shifts.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The quantum Potts spin chain is not integrable apart from the critical point. Nevertheless, its spectrum can easily be guessed, and subsequently verified using perturbation theory for g far away from the critical value [35]. In the ferromagnetic phase, the elementary excitations are domain walls with dispersion relation…”
Section: On the Spin Chainmentioning
confidence: 96%
“…For more information regarding the quasi-particle spectrum of the chain we refer the interested reader to the work [49] and references therein.…”
Section: Entanglement Growth Ratementioning
confidence: 99%